UJI TOKSISITAS AKUT (LETHAL DOSE50) EKSTRAK ETANOL DAUN GEDI MERAH (Abelmoschus manihot L.) TERHADAP TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus L.) - Assagaf, Fadhila; Wullur, Adeanne; Yudistira, Adithya (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACT This study aimed to determine the acute toxicity Lethal Dose50 of red aibika (Abelmoschus Manihot L.) leaves extract against white males rats (Rattus norvegicus L.) wistar strain. The method used was controlled group post-test only design. Subject were white male white rats with a total of 20 and divided into 5 groups: namely group 1 as a positive control, group 2 was treated 40% red aibeka leaf extract, g, group 3 was treated 60% red aibeka leaf extract, , group 4 was treated 80% red aibeka leaf extract, and , group 5 was treated 100% red aibeka leaf extract,. Data was recorded when there was a death in rats after a given treatment. LD50 calculation formula according to Thomson and Weil Method to calculate the LD50 value of red aibeka leaf extract. The results showed that mortality in the entire group 4 and 5 of tested animal occurred after treatment with LD50 values of 6,25 g/KgBB. It can be concluded that the leaf extracts of red aibika slightly toxic to the male white rat wistar strain. Keywords: Abelmoschus Manihot L., Red aibika, Acute Toxicity Test, Lethal Dose 50 (LD50).